A novel reverse transcription recombinase polymerase amplification assay for rapid detection of GI.1 genotype of rabbit hemorrhagic disease virus - Zhang, Lianzhi; Zhao, Qiaoya; Tian, Ye; Tang, Yi; Wang, Yixin; Huang, Bing (Frontiers in Veterinary Science, 2023)
Rabbit viral hemorrhagic disease (RHD) is a highly pathogenic and fatal infectious disease, leading to significant economic loss to the rabbit industry. In this study, a rapid simple reverse transcriptase recombinase polymerase amplification (RT-RPA) for RHDV GI.1 was successfully developed using specific primers to RHDV GI.1 VP60 gene. Also, the entire amplification process could be completed in the isothermal condition at 40℃ for 30min, the method had good specificity with no reaction to other common rabbit disease pathogens, and high sensitivity upto 0.1LD50 of RHDV GI.1. And then 1144 nasal swab samples were detected from different rabbit farms in Shandong Province by RT-RPA. The result showed that the positive rate was 0.95%, 1.29%, 2.50% in Zaozhuang, Linyi, Liaocheng, respectively (the Fisher's exact test, P=0.413), indicating that there was no significant difference in RHDV GI.1 infection in different regions. The RT-RPA assay could be suitable for rapid detection and epidemiological surveillance of RHDV GI.1.